The Urgency of Methodological Integration between Hermeneutics and Tafsir in Understanding The Qurʾān - Piet Hizbullah Khaidir; Uun Yusufa; Amiruddin Hadi Wibowo (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: For the purpose of developing a comprehensive method of interpreting the Qur'an, Al-Qur'an researchers have written research manuscripts containing criticism of exegetical and hermeneutical methods. However, the weakness of this criticism is that it only focuses on the weak points of the two methods. This research explores data regarding criticism of the two methods of interpreting the Qur'an by showing the weaknesses and strengths of both. For the purpose of finding a comprehensive method of interpreting the Qur'an, this paper proposes the possibility of integration between the two methods. The method used in this research is descriptive-analytical within the framework of a literature study. With this method, tafsir and hermeneutical methods are described and analyzed based on literature reviews or literature studies of both. Next, there is a proposed methodological alternatives within the framework of integrating the two methods. The conclusion from this research is that it is very possible to integrate the two methods to obtain a comprehensive interpretation method. Regarding the possibility of integration, this research offers a method of interpreting the Qur'an namely Interpretive Exegetical Methodology.